ANALISIS PENERIMAAN DIRI ISTRI YANG MENGALAMI DISENFRANCHISED GRIEF (Studi Kasus pada ODHA Perempuan) - Kartika Indradjaja (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2013)
In Indonesia, the most number of HIV cases on ODHA (People who live with HIV/AIDS) women found among housewives who are infected through heterosexual intercourse. Most housewives know their ODHA status after their husbands passed away, which directly cause disenfranchised grief because the grief could not be freely expressed, in result of negative thinking of HIV it self. This research is done prior to analyze adaptation process of housewives who experienced disenfranchised grief along with the HIV disease.Research is done through qualitative approach with case study method to 3 participants. Result of the research shows that acceptance stage can be reached if each individual get enough support from environment and have high extraversion level of personality. On the other hand, participant who does not get any social support together with high neuroticism level and low extraversion personality, is likely not able to cope up with current condition, therefore adaptation process still on denial stage and be accompanied with number of irrational beliefs. However, enough social support does not guarantee acceptance stage is going to occur if it is followed by impulsive, childish, and self centered personality. Further result of research shows that individual with positive self acceptance generate higher quality of life.